Perceived public health threat a key factor for willingness to get the COVID-19 vaccine in Australia. Issue 17 (14th April 2022) - Dodd, Rachael H.; Pickles, Kristen; Cvejic, Erin; Cornell, Samuel; Isautier, Jennifer M.J.; Copp, Tessa; Nickel, Brooke; Bonner, Carissa; Batcup, Carys; Muscat, Danielle M.; Ayre, Julie; McCaffery, Kirsten J.
Highlights: Perceived public health threat is associated with intentions to vaccinate. Those believing the efficacy of vaccines is made up were less willing to get vaccinated. To protect myself and others was the top reason for getting the vaccine. Safety concerns was the top reason against getting the vaccine. Abstract: Background: Vaccination rollout against COVID-19 is underway across multiple countries worldwide. Although the vaccine is free, rollout might still be compromised by hesitancy or concerns about COVID-19 vaccines. Methods: We conducted two online surveys of Australian adults in April (during national lockdown; convenience cross-sectional sample) and November (very few cases of COVID-19; nationally representative sample) 2020, prior to vaccine rollout. We asked about intentions to have a potential COVID-19 vaccine (If a COVID-19 vaccine becomes available, I will get it) and free-text responses (November only). Results: After adjustment for differences in sample demographics, the estimated proportion agreeing to a COVID-19 vaccine if it became available in April (n = 1146) was 76.3%. In November (n = 1941) this was estimated at 71.5% of the sample; additional analyses identified that the variation was driven by differences in perceived public health threat between April and November. Across both surveys, female gender, being younger, having inadequate health literacy and lower education were associated with reluctance to be vaccinated against COVID-19. Lower perceived susceptibility to COVID-19, belief that data on the efficacy of vaccines is 'largely made up', having lower confidence in government, and lower perception of COVID-19 as a public health threat, were also associated with reluctance to be vaccinated against COVID-19. The top three reasons for agreeing to vaccinate (November only) were to protect myself and others, moral responsibility, and having no reason not to get it. For those who were indifferent or disagreeing to vaccinate, safety concerns were the top reason, followed by indecision and lack of trust in the vaccine respectively. Conclusions: These findings highlight some factors related to willingness to accept a COVID-19 vaccine prior to one being available in Australia. Now that the vaccine is being offered, this study identifies key issues that can inform public health messaging to address vaccine hesitancy.